Does Context Matter? Mastery Motivation and Therapy Engagement of Children with Cerebral Palsy - Miller, L.; Ziviani, J.; Ware, R.; Boyd, Roslyn (Informa Healthcare, 2015)
Aims: To determine if mastery motivation at baseline predicts engagement in two goal-directed upper limb (UL) interventions for children with unilateral cerebral palsy (UCP). Methods: Participants were 44 children with UCP, mean age 7 years 10 months, Manual Ability Classification System level I (N = 23) or II (N = 21). Twenty-six children received intensive novel group-based intervention (Hybrid Constraint Induced Movement Therapy, hCIMT) and 18 received distributed individual occupational therapy (OT). Caregivers completed the Dimensions of Mastery Questionnaire (DMQ) parent-proxy report at baseline. Children's engagement was independently rated using the Pediatric Volitional Questionnaire (PVQ). Associations between children's mastery motivation and engagement were examined using linear regression. Results: Children who received hCIMT had lower DMQ persistence at baseline (p = .05) yet higher PVQ volitional (p = .04) and exploration (p = .001) scores. Among children who received hCIMT, greater object-oriented persistence was associated with task-directedness (β 0.25, p = .05), seeking challenges (β = 0.51, p = .02), exploration (β = 0.10, p = .03), and volitional scores (β = 0.23, p = .01). Conclusion: Despite having lower levels of persistence prior to engaging in UL interventions, children who received hCIMT demonstrated greater engagement in goal-directed tasks than children who received individual OT. Within hCIMT, children's motivational predisposition to persist with tasks manifested in their exploration and engagement in therapy.